Biological Diversity and Sustainable Resources Use - Grillo, Oscar; Venora, Gianfranco (IntechOpen, 2011)
Biological Diversity and Sustainable Resources Use is a very interesting volume, including attractive overviews and original case studies mainly focused on socio-economical effects of the right management of the ecosystems biodiversity, as well as on the useful integration between human activities and environmental responses. Ecological, medical and historical aspects of the sustainable development are also discussed in this book which consists of articles written by international experts, offering the reader a clear and extensive view of the present condition in which our planet is.